Efficiency improvement of Roots vacuum pump working process: Computational fluid dynamics methods modeling - Burmistrov, Aleksey; Raykov, Alexey; Isaev, Aleksandr; Salikeev, Sergey; Kapustin, E.; Fomina, Marina (Vakuum in Forschung und Praxis : Zeitschrift für Vakuumtechnologie, Oberflèachen und Dünne Schichten, 2022)
In this paper influence of rotor profile type of Roots vacuum pumps on backward leakage through channels of rotor mechanism and pumping speed is considered. Elliptical, involute, and circular profiles are widely used. Backward leakage through channels of rotor mechanism with different rotor profiles is determined from conductance which was calculated by angular coefficients method for free molecular flow regime at different rotors rotating angles. It is shown that backward leakage is maximal at rotors rotating angles 25–45° due to maximal inter‐rotor channel opening for gas flow and is minimal at 0°. Elliptical rotor profile provides minimal backward leakage over one revolution. Numerical modeling of Roots pump working process was carried out on the basis of CFD ANSYS‐CFX complex by dynamic meshing method. SST turbulence model was used for calculations. It is confirmed that maximal pumping speed is provided by Roots pump with elliptical rotor profile. Verbesserung der Effizienz von Wälzkolbenvakuumpumpen Der Einfluss des Rotorprofils von Wälzkolbenpumpen auf die Rückwärtsleckage durch Kanäle des Rotormechanismus und auf das Saugvermögen wird untersucht. Für die häufig verwendeten elliptischen, evolventen‐und kreisförmigen Profile wird der Rückfluss aus dem Leitwert bestimmt, der für verschiedenen Rotordrehwinkeln mittels Angular Coefficient Method – einem Verfahren zur Betrachtung der freien Molekülströmung – ermittelt wird. Es wird gezeigt, dass ein elliptisches Rotorprofil für minimale Rückwärtsleckage bei einer Umdrehung sorgt.